SLAMETAN METRI: Studi Kasus di Dusun Ngelgok Desa Kranding Kecamatan Mojo Kabupaten Kediri Jawa Timur - Mustakim Mustakim (Bahasa Indonesia, 2022)
Javanese people have a lot of cultures that have become extinct or are rarely practiced by them population nowdays, one of which is the slametan metri. This research was conducted from 1998 to 2019 in the Ngelgok, Kranding, Mojo, Kediri. It is long duration of the study because most people did not preserve slametan. The momentum does not always occur each year or month. Thereforethe researcher used the anthropology-insider approach to find the right and complete conclusions from 1998 to 2019. The results of this research are six types of metri. First, metri to people who migrate. Second, metri to people getting disaster. Third, metri to people getting nightmare. Fourth, metri to people buying a new vehicle. Fifth, metri to people getting position and sixth, weton metri.